Antipsychotic treatments; focus on lurasidone - Sumiyoshi, Tomiki (Frontiers in Pharmacology, 2013)
The introduction of atypical antipsychotic drugs (AAPDs), or second-generation antipsychotics, with clozapine as the prototype, has largely changed the clinicians’ attitudes towards the treatment of mental illnesses including, but not limited to schizophrenia. Initially, there was optimism that AAPDs would be superior over typical antipsychotic drugs (TAPDs), or first-generation antipsychotic drugs, in terms of efficacy for various phenomenological aspects, including cognitive impairment, and less likelihood of causing adverse events. However, these views have been partly challenged by results from recent meta-analysis studies. Specifically, cardio-metabolic side effects of AAPDs, in spite of a relative paucity of extrapyramidal symptoms, may sometimes limit the use of these agents. Accordingly, attempts have been made to develop newer compounds, e.g. lurasidone, with the aim of increasing efficacy and tolerability. Further investigations are warranted to determine if a larger proportion of patients will be benefitted by treatment with AAPDs compared to TAPDs in terms of remission and recovery.